Exploring the impact on faculty of the American Association of Colleges of Nursing's The Essentials: Core Competencies for Professional Nursing Education. - Pearson, Mary Cassandra; Shumway, Jennifer (Journal of Professional Nursing, 2025)
Current nursing instructional methods inadequately prepare students for complex healthcare settings, exacerbating challenges in new graduate competency and transition to practice. The introduction of standardized competencies marks a substantial shift in nursing education, posing a considerable challenge for faculty implementing these changes. This study examined the experiences of faculty implementing a competency-based education program utilizing The Essentials: Core Competencies for Professional Nursing Education (2021) in undergraduate Bachelor of Science in Nursing (BSN) education programs. A qualitative research design using phenomenology was chosen to explore the experiences of eight faculty and gain insight into perceived challenges experienced during the implementation of The Essentials recommendations through semi-structured interviews. Data was analyzed using a manual content analysis with a constant comparative technique. The data analysis revealed three primary themes focused on the faculty's initial uncertainty, the challenges associated with change processes and faculty engagement, and the strategies employed to develop and implement a competency-based program. The findings provide insight into the faculty experience during The Essentials implementation, proposing strategies for curriculum alignment and overcoming resistance to change. Faculty continue to seek validation for their work while also facing the challenge of balancing implementation demands and broader institutional responsibilities. Continued discussions on faculty role development and resource identification are essential for future competency-based education program advancements. • New recommendations to transform nursing education include competency-based education. • Implementing standardized competencies dramatically changes nursing education. • The Essentials alignment occurred through mapping and modifying current curriculum. • Fear, uncertainty, faculty buy-in, and institutional culture impacted change efforts. • Program development needs resources, validation, time, and administrative support.